FREQUENCY OF RADIAL NERVE INJURY IN PATIENTS WITH CLOSED FRACTURE OF HUMERUS SHAFT IN HIGH ENERGY TRAUMA CASES - Muhammad Muazzam Khan,; Muhammad Ali,; Jemal Girma,; Muhammad Umer Faheem,; Ashfaq Jadoon,; Amer Aziz, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Fracture of the humerus usually result in radial nerve injury. This study was done with the aim to determine the incidence of Radial Nerve Injury in patients with closed fracture of the humerus shaft in high-energy trauma cases. Methods: This descriptive study was conducted in the Department of Orthopedics and Emergency room, Ghurki Teaching Hospital, Lahore from January to December 2021 recruiting consecutive such patients. Standard ward protocol was followed to manage the patients initially including fracture stabilization and analgesia requirement. All the patients were carefully assessed to detect radial nerve injury. Data analysis was done through SPSS 26.0. Results: A total of 80 patients were included with the confirmed diagnosis of fracture of the humerus. There were 55(68.5%) males and 25(31.25%) females. The age range was 20 to 60 years and the mean age of males and females was 31.62±8.35 and 38.43±5.06 respectively with overall mean age±SD was 38.93±6.19. There were 32 (40%) cases of spiral fracture, 17 (21.25%) cases of transverse fracture, 16 (20%) cases of communized fracture, and 15 (18.75%) cases of segmental fracture. Radial nerve injury was present in 7 (8.75%) patients. Out of these 7 cases of radial nerve injury; 4 (57.1%) cases were recorded in patients with spiral closed fracture of midshaft of humerus, 1 (14.3%) cases were recorded in transverse closed fracture of humerus shaft, 1(14.3%) cases in comminuted closed fracture of midshaft of the humerus while 1 (14.3%) were segmental fractures. Conclusion: Our study highlighted the frequency of radial nerve palsy in humeral shaft cases with most common in spiral closed fracture of the midshaft of the humerus.